2022
DOI: 10.1057/s41292-022-00285-5
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of multimorbidity as a matter of concern: a critical review

Abstract: Multimorbidity is considered one of the greatest emerging challenges for contemporary health care systems. However, the meaning of the term ‘multimorbidity’ is not straightforward. Despite many attempts to clarify the definition and its measurement, the concept remains elusive. Still, academic interest in the study of multimorbidity has grown exponentially in the past ten years. In this paper, we trace the emergence of multimorbidity as a ‘matter of concern’ within health care research, exploring what has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…Our intention was not to synthesise all that has been published about multimorbidity, but rather to understand how multimorbidity is crystallising as a concept and field of study in the context of global health. As such, rather than adopting a structured framework designed to capture the entire domain of multimorbidity, we followed the approach of similar reviews on multimorbidity 10 and other health issues 11 , 13 that utilised a more open-ended, exploratory approach to the identification and synthesis of literature. This allowed us to trace how multimorbidity is being constructed as an object of science, policy, and care across a variety of bodies of literature in a way that is not facilitated by more structured literature review approaches.…”
Section: Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…Our intention was not to synthesise all that has been published about multimorbidity, but rather to understand how multimorbidity is crystallising as a concept and field of study in the context of global health. As such, rather than adopting a structured framework designed to capture the entire domain of multimorbidity, we followed the approach of similar reviews on multimorbidity 10 and other health issues 11 , 13 that utilised a more open-ended, exploratory approach to the identification and synthesis of literature. This allowed us to trace how multimorbidity is being constructed as an object of science, policy, and care across a variety of bodies of literature in a way that is not facilitated by more structured literature review approaches.…”
Section: Approachmentioning
confidence: 99%
“…21 It is notable against this backdrop that a recent review of narratives and responses to multimorbidity has shown that its apparent rise may be as much an artefact of the expansion of disease and risk categories within biomedicine as much as any ‘true’ rise in disease burdens. 10 This not only leads to habitual overdiagnosis and ‘polypharmacy’, presenting challenges for patients and providers at the clinical level. 10 , 23 The new configurations of risk and responsibility enabled by these categories also makes disease classification pivotal to the extension of modern political power at the population level.…”
Section: Making and Managing Morbiditymentioning
confidence: 99%
See 3 more Smart Citations